PERAN DITJEN POTHAN KEMENTERIAN PERTAHANAN RI TERHADAP URGENSI PENDIDIKAN BELA NEGARA GUNA MEMBANGUN SIKAP NASIONALISME PADA GENERASI MILLENIAL / MAHASISWA DI INDONESIA - Ahmad Nur Ahsan; Muchammad Hifni (JURNAL MAHATVAVIRYA, 2022)
This study provides an explanation of the relationship between defending the state and national security is the relationship that already exists between the two aspects. Both of them can realize all the hopes and goals of the state as stated in a regulation in the Republic of Indonesia, this is in the form of a preamble to an opening contained in the 1945 Constitution of the Republic of Indonesia in paragraph IV. Defending the state is in the form of efforts made in the real form of defending a country that is driven through a form called determination, attitude and a strong spirit of fighting power and concrete steps by all citizens who have been correct in an organized and integrated manner which is imbued with the Unitary State of the Republic of Indonesia. The main thing is based on Pancasila and the 1945 Constitution of the Republic of Indonesia. National resilience which has been understood together in a literal sense is to have the meaning of a condition that has a good or dynamic element of a nation based on a strong tenacity and good toughness in which it contains an ability to always can develop strength in the national sphere and overcome all kinds of real infiltration of challenges, threats, obstacles, and disturbances, both of which always come from outside and from within, directly or indirectly, jeopardizing integrity in realizing state goals.